Duty Factor Is a Viable Measure to Classify Spontaneous Running Forms - Patoz, Aurélien (Sports (Basel), 2019)
Runners were classified using two different methods based on their spontaneous running form: (1) subjectively using the V(®)score from the Volodalen(®) scale, leading to terrestrial and aerial groups; and (2) objectively using the duty factor (DF), leading to high (DF(high)) and low (DF(low)) DF groups. This study aimed to compare these two classification schemes. Eighty-nine runners were divided in two groups using the V(®)score (VOL groups) and were also ranked according to their DF. They ran on a treadmill at 12 km·h(−1) with simultaneous recording of running kinematics, using a three-dimensional motion capture system. DF was computed from data as the ratio of ground contact time to stride time. The agreement (95% confidence interval) between VOL and DF groups was 79.8% (69.9%, 87.6%), with relatively high sensitivity (81.6% (68.0%, 91.2%)) and specificity (77.5% (61.6%, 89.2%)). Our results suggest that the DF and V(®)score reflect similar constructs and lead to similar subgroupings of spontaneous running form (aerial runners if DF < 27.6% and terrestrial runners if DF > 28.8% at 12 km·h(−1)). These results suggest that DF could be a useful objective measure to monitor real-time changes in spontaneous running form using wearable technology. As a forward-looking statement, spontaneous changes in running form during racing or training could assist in identifying fatigue or changes in environmental conditions, allowing for a better understanding of runners.